2013
DOI: 10.1590/s1516-89132013000100017
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of Pb and Cd in seafood by ICP OES with on-line pre-concentration by solid phase extraction with amberlite XAD-4 after complex formation with DDTP

Abstract: An on-line method for Cd and Pb pre-concentration and simultaneous determination in acid digested seafood by inductively coupled plasma optical emission spectrometry (ICP OES)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies have reported the concentration and toxicity of cadmium in shrimps (Páez-Osuna and Ruíz-Fernández, 1995b;Páez-Osuna and Tron-Mayen, 1996;Vanegas et al, 1997;Soegianto et al, 1999;Pourang and Amini, 2001;Kargin et al, 2001;Pourang et al, 2004;Wu and Chen, 2004;Seebaugh et al, 2005;Santos et al, 2013). The Cd concentrations in the shrimp body depend mainly on their levels in the environment since this element is not essential in the biochemical and physiological processes of this animal (Ruelas-Inzunza and Páez-Osuna, 2004).…”
Section: Distribution Of Trace Elements In Tissuesmentioning
confidence: 99%
“…Several studies have reported the concentration and toxicity of cadmium in shrimps (Páez-Osuna and Ruíz-Fernández, 1995b;Páez-Osuna and Tron-Mayen, 1996;Vanegas et al, 1997;Soegianto et al, 1999;Pourang and Amini, 2001;Kargin et al, 2001;Pourang et al, 2004;Wu and Chen, 2004;Seebaugh et al, 2005;Santos et al, 2013). The Cd concentrations in the shrimp body depend mainly on their levels in the environment since this element is not essential in the biochemical and physiological processes of this animal (Ruelas-Inzunza and Páez-Osuna, 2004).…”
Section: Distribution Of Trace Elements In Tissuesmentioning
confidence: 99%
“…Therefore, it can be said that a well-chosen adsorbent determines the efficiency of the SPE technique. Amberlite 2 Journal of Chemistry XAD5 resins which are able to adsorb metal complexes have received a great deal of attention because of versatile usage with or without derivatization [19][20][21][22]. In particular, Amberlite XAD-7 resin possessing an intermediate polarity and hydrophilic surface as a highly crosslinked macroreticular acrylic resin (polyacrylic acid ester polymer) has been performed in SPE studies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%